Implementation of Project Based Learning Model with Product Differentiation Approach to Improve Negotiation Text Writing Skills of Grade X Students of SMA Negeri 2 Medan - Mutiawati Wati; Rita (LITERATUR : Jurnal Bahasa dan Sastra, 2025)
This study is a Classroom Action Research (CAR) that aims to improve negotiation text writing skills through a project-based learning model with a differentiated product approach and a differentiated learning approach for 10th grade students. This study was conducted at SMA Negeri 2 Medan with 36 10th grade students as the research subjects. There were 19 male students and 17 female students. The research method used qualitative and quantitative research. The research data were analyzed using qualitative and quantitative descriptive analysis. The results of the data analysis were then presented in tables and figures/charts. The results showed that the application of PjBL significantly improved students' writing skills and encouraged the development of creativity, collaboration, and critical thinking skills. In addition, students reported an increase in motivation and activity in the learning process. However, challenges in implementing PjBL, such as the need for thorough preparation by teachers and effective time management, need to be considered. Based on the results of the analysis, it was concluded that PjBL is an effective method for improving students' writing skills and can be integrated into Indonesian language learning to create a more interesting and meaningful learning experience. The results of this study emphasize that PjBL is an effective, innovative, and relevant learning method for equipping students with 21st-century skills.